Інвестиції у відбудову Свірзького замку на сучасному етапі: можливості фінансування - Криворучко, Я. Ю.; Шуляр, Ю. В.; Kryvorychko, J. J.; Shuliar, J. V. (Видавництво Національного університету “Львівська політехніка”, 2005)
Проаналізовано сучасний стан замку у с. Свірж і можливостей фінансування його подальшої відбудови і введення в експлуатацію.

The actuality of taking measures for exploration of historical ensembles, their saving and adjustment to the contemporary needs on the example of Ukrainian castles is considered. Involving youth groups in different actions, particularly historical musical festivals, exhibitions and so on in the historical environment, or its artificial variant makes the architectural heritage popular and consolidates young people – members of youth organizations and clubs, guests and spectators.
Modern utilization of medieval castles by youth organizations
Keywords: замок; історія; законодавство; інвестори; фінансування; 624